2006
DOI: 10.1002/dys.327
|View full text |Cite
|
Sign up to set email alerts
|

Language‐related differences between discrepancy‐defined and non‐discrepancy‐defined poor readers: a longitudinal study of dyslexia in New Zealand

Abstract: Language-related differences between discrepancy-defined and non-discrepancy-defined poor readers were examined in a three-year longitudinal study that began at school entry. The discrepancy-defined (dyslexic) poor readers (n=19) were identified in terms of poor reading comprehension and average or above average listening comprehension performance, and the non-discrepancy-defined (non-dyslexic) poor readers (n=19) in terms of both poor reading and listening comprehension performance. The two poor reader groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…In support of this claim, Tunmer and Chapman (2007) found in a longitudinal study of language-related differences between mixed disabled readers and dyslexic poor readers that in addition to expected differences on oral language measures, the mixed disabled readers also showed consistently greater phonological processing deficits than the dyslexic poor readers across a range of phonological processing measures (see Snowling, Gallagher, & Frith, 2003, for similar findings).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…In support of this claim, Tunmer and Chapman (2007) found in a longitudinal study of language-related differences between mixed disabled readers and dyslexic poor readers that in addition to expected differences on oral language measures, the mixed disabled readers also showed consistently greater phonological processing deficits than the dyslexic poor readers across a range of phonological processing measures (see Snowling, Gallagher, & Frith, 2003, for similar findings).…”
mentioning
confidence: 52%
“…These children, who are also called ''garden variety'' poor readers (Gough & Tunmer, 1986), have more widespread language impairments than are typically found among children with dyslexia (Catts & Kamhi, 2005;Tunmer & Chapman, 2007). In addition to phonological processing deficits, children with mixed reading disability have impairments in vocabulary, morphology, syntax, and/or discourse-level processing.…”
mentioning
confidence: 98%
“…According to the study of Weinberg et al [24], the performance of good readers was not affected by listening also. Generally, the difficulty in reading is based on the factors such as dyslexia, deficits in the development of phonological representations and IQ [6,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tunmer and Chapman (2007) provided empirical evidence arguing against the premise of the discrepancy definition when they tracked phonological processing, language and reading skills for 91 children over the first three years of formal schooling. Poor readers selected on the basis of being discrepancy-defined or non discrepancy-defined, all had phonological processing deficits.…”
Section: The Shift Away From the Discrepancy Definition Modelmentioning
confidence: 99%
“…Links between many aspects of oral language and reading achievement have been well established for some time (Bradley & Bryant, 1983;Catts et al, 1999Catts et al, , 2002Fletcher et al, 1994;Georgiou, Parilla, & Kirby, 2006;Goswami & Bryant, 1990;Stuart, 2005;Tunmer & Chapman, 2007;Vellutino, Scanlon, Small, & Tanzman, 1991). Further, it has been demonstrated that oral language capacity prior to school entry, substantially contributes towards predicting reading achievement once formal instruction commences (Boudreau & Hedberg, 1999;Catts et al, 1999Catts et al, , 2002Paul, 2007;Justice, Invernizzi, & Meier, 2002;Snowling, Bishop, & Stothard, 2000;Vellutino et al, 1991).…”
Section: Introductionmentioning
confidence: 94%